90. Impact of Discrepant Rapid Diagnostic Test (RDT) Results on Antimicrobial Stewardship Program (ASP) Interventions in Patients with Bloodstream Infections (BSI) due to Gram-Negative Bacilli (GNB). (31st December 2020) - Robinson, Evan D; Cox, Heather L; Attai, April E; Donohue, Lindsay; Shah, Megan; Hill, Brandon; Elliott, Zach; Mathers, Amy J; Mathers, Amy J
Abstract: Background: Implementation of the Accelerate Pheno TM Gram-negative platform (AXDX) paired with ASP intervention projects to improve time to definitive institutional-preferred antimicrobial therapy (IPT). However, few data describe the impact of discrepant RDT results from standard of care (SOC) methods on antimicrobial prescribing. Here we evaluate the prescribing outcomes for discrepant results following the first year of AXDX + ASP implementation. Methods: Consecutive, non-duplicate blood cultures for adult inpatients with GNB BSI following combined RDT + ASP intervention were included (July 2018 – July 2019). AXDX results were emailed to the ASP in real time then released into the EMR upon ASP review and communication with the treating team. SOC identification (ID; Vitek® MS/Vitek® 2) and antimicrobial susceptibility testing (AST; Trek Sensititre TM ) followed RDT as the reference standard. IPT was defined as the narrowest susceptible beta-lactam, and a discrepancy was characterized when there was categorical disagreement between RDT and SOC methods. When IPT by AXDX was found to be non-susceptible on SOC, this was characterized as "false susceptible". Conversely, "false resistance" was assessed when a narrower-spectrum agent was susceptible by SOC. Results were also deemed discrepant when the AXDX provided no/incorrect ID for on-panel organisms, no AST, or a polymicrobial specimen was missed. Results: Sixty-nine of 250 patients (28%) had a discrepancy in organism ID or AST: false resistance (9%), false susceptible (5%), no AST (5%), no ID (4%), incorrect ID (2%), and missed polymicrobial (2%). A prescribing impact occurred in 55% of cases (Table 1), where unnecessarily broad therapy was continued most often. Erroneous escalation (7%) and de-escalation to inactive therapy (7%) occurred less frequently. In-hospital mortality occurred in 4 cases, none of which followed an inappropriate transition to inactive therapy. Conclusion: Though the AXDX platform provides rapid ID and AST results, close coordination with Clinical Microbiology and continued ASP follow up are needed to optimize therapy. Although uncommon, the potential for erroneous ASP recommendations to de-escalate to inactive therapy following AXDX results warrants further investigation. Disclosures: Amy J. Mathers, MD, D(ABMM), Accelerate Diagnostics (Consultant)